Pengaruh Rekrutmen dan Penempatan Kerja terhadap Produktivitas Kerja Karyawan pada PT. Sindang Brothers Kota Lubuklinggau - Wisdalia Maya Sari (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2018)
Success or failure of the organization in achieving the goals set previously depends on the ability of human resources (employees) in carrying out the task or work given. This study aims to determine the effect of recruitment and job placement on employee productivity at PT.Sindang Brothers Lubuklinggau City. The method of data processing was saturated sampling approach that is the sampling method that the entire population amount is used as research sample which amounted to 47 employees. Data analysis conducted by validity and reliability test, normality test, classical assumption test, simple linear regression test, determination test, F test and T test. Based on the result of research, it is concluded that Recruitment and Work Placement partially have significant effect on Work Productivity at PT. Sindang Brothers Town of Lubuklinggau. The effect of recruitment on work productivity is 83.6% and the remaining 16.4 is influenced by other variable variables outside the research. While the effect of placement on work productivity is 87.6 percent and the rest 12.4 is influenced by other variable variables. Keywords: Recruitment, Job Placement, and Work Productivity